Intellectual Humility as A Predictor of Conflict Resolution in Government Policy Acceptance in the Situation of the Covid-19 Pandemic in Indonesia - Arlita Permanasari; Araminta Permatasari (International Journal of Social Service and Research, 2023)
The spread of Covid-19 in Indonesia shows a relatively high increase throughout the Pandemic. The government is trying to run various programs to break the chain of transmission of Covid-19, but the refusal of some people makes controlling the pandemic more difficult to achieve. The spread of hoax news and oppositional attitudes towards the government also influenced public rejection. This condition also increases the escalation of conflict between the government and some community groups. Proven in this study, intellectual humility correlates with the formation of conflict resolution, so it can be a good predictor in seeing public acceptance of government policies, especially related to the determination of interventions to groups that are not cooperative with Covid-19 response. This research is participatory, with a phenomenological framework whose data is converted into quantitative. Next, it is analyzed using parametric statistical calculations.